2017
DOI: 10.1139/cjfr-2016-0209
|View full text |Cite
|
Sign up to set email alerts
|

Mapping site index and volume increment from forest inventory, Landsat, and ecological variables in Tahoe National Forest, California, USA

Abstract: High-resolution site index (SI) and mean annual increment (MAI) maps are desired for local forest management. We integrated field inventory, Landsat, and ecological variables to produce 30 m SI and MAI maps for the Tahoe National Forest (TNF) where different tree species coexist. We converted species-specific SI using adjustment factors. Then, the SI map was produced by (i) intensifying plots to expand the training sets to more climatic, topographic, soil, and forest reflective classes, (ii) using results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Researchers often integrate field inventory data with coarseresolution imagery through imputation models to map detailed forest attributes over large areas (Beaudoin et al 2014;Blackard et al 2008;Huang et al 2017;Wilson et al 2012;Zhang et al 2014). One widely used approach is k nearest neighbor (kNN) imputation (Tomppo et al 2008;Zald et al 2014), which uses a set of predictor variables (x) to determine a number (k) of most similar reference observations (nearest neighbors or NN) to derive response variables (y) for the target pixel (Crookston and Finley 2008;McRoberts 2012;Ohmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers often integrate field inventory data with coarseresolution imagery through imputation models to map detailed forest attributes over large areas (Beaudoin et al 2014;Blackard et al 2008;Huang et al 2017;Wilson et al 2012;Zhang et al 2014). One widely used approach is k nearest neighbor (kNN) imputation (Tomppo et al 2008;Zald et al 2014), which uses a set of predictor variables (x) to determine a number (k) of most similar reference observations (nearest neighbors or NN) to derive response variables (y) for the target pixel (Crookston and Finley 2008;McRoberts 2012;Ohmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For soil, productivity classes were compiled from the Soil Survey Geographic (SSURGO) database. These data sets were described in Huang, Ramirez, Conway, et al (2016) and Huang et al (2018).…”
Section: Earth and Space Sciencementioning
confidence: 99%
“…As outlined in previous studies (Huang, Ramirez, Conway, et al, 2016;Huang et al, 2018), remote sensing images must be sensitive and correlated to both pre-and postdisturbance forest conditions. Different types of disturbances can result in considerable variation in terms of internal patterns of mortality and the amount of biological material that can contribute to ecosystem recovery (Foster et al, 1998).…”
Section: Remote Sensing Data Choicesmentioning
confidence: 99%
“…Moreover, several studies have reported site indices for prediction and mapping based on a limited number of factors that can be easily derived from remote sensing data, such as Landsat (Günlü et al, 2008;Huang et al, 2017) Detection And Ranging (LiDAR) (Laamrani et al, 2014). Spatially continuous maps are needed for tactical planning and operations for forest management;…”
Section: Introductionmentioning
confidence: 99%
“…therefore, high-resolution site index maps are very powerful tools for local forest management (Huang et al, 2017). In Japan, it has become possible to estimate the site index using topographic factors derived from DEM, especially for conifer plantations of trees, such as the Japanese larch (Larix kaempferi) (Mitsuda et al, 2001), Japanese cedar (Cryptomeria japonica) (Zushi, 2006;Mitsuda et al, 2007).…”
Section: Introductionmentioning
confidence: 99%